Characterizing Wildland Firefighters’ Thermal Environment During Live-Fire Suppression - Carballo-Leyenda, Belén; Villa, José G.; López-Satué, Jorge; Rodríguez-Marroyo, Jose A. (Frontiers in Physiology, 2019)
Wildland firefighters work under adverse environments (e.g. heat and fire exposure), which contribute to increasing the heat strain. Despite this there is a paucity of knowledge about the thermal environment in real wildfire suppression scenarios. Therefore, the main purpose of this study was to characterize the environmental thermal exposure and the risk of heat burn injuries during real wildfire suppression (n=23). To characterize the wildland firefighter’s (n=5) local thermal exposure, measurements of air temperature and heat flux were performed. Heat flux measurements were made using four thin-planar heat flux sensors. Two were affixed on the outer surface of the garment on the left chest and thigh. Two other sensors were placed on the inner surface of the fabric in parallel to those placed externally. Four thermal classes were defined based on the heat flux across the inner sensors (≤1000, ≤5000, ≤7000 and >7000 W·m-2). The risk of pain and first-degree burns were calculated using the dose of thermal radiation method. The inner sensors mean and maximum heat flux and environment temperature were 286.7 ± 255.0 & 2370.4 ± 3004.5 W·m-2 and 32.6 ± 8.9 & 78.0 ± 8.9 ºC, respectively. Approximately 81, 15 and 3.5% of the exposure time the heat flux was ≤1000, >1000–5000 and >5000 W·m-2, respectively. The highest average and maximum thermal dose values were ~94 and ~110 (kW·m-2)4/3·s. In conclusion, the thermal exposure obtained may be considered light. However, high thermal exposure values may be obtained in punctual moments, which can elicit first-degree burns.